Impact of Antenatal Steroids on Intraventricular Hemorrhage in Very Low Birth Weight Infants - Wei, Julia C. (J Perinatol, 2016)
OBJECTIVE: To determine the association between antenatal steroids administration and intraventricular hemorrhage rates. METHODS: We used cross-sectional data from the California Perinatal Quality Care Collaborative during 2007-2013 for infants ≤ 32 weeks gestational age. Using multivariable logistic regression, we evaluated the effect of antenatal steroids on intraventricular hemorrhage, stratified by gestational age. RESULTS: In 25,979 very low birth weight infants, antenatal steroid use was associated with a reduction in incidence of any grade of intraventricular hemorrhage (odds ratio = 0.51, 95% confidence interval: 0.45, 0.58) and a reduction in incidence of severe intraventricular hemorrhage (odds ratio = 0.62, 95% confidence interval: 0.57, 0.67). This association was seen across gestational ages ranging from 22 to 29 weeks. CONCLUSIONS: While current guidelines recommend coverage for preterm birth at 24 to 34 weeks gestation, our results suggest that treatment with antenatal steroids may be beneficial even before 24 weeks of gestational age.